Socialisation of the student nurse in the nursing profession - F.J. Bezuidenhout (AOSIS, 1982)
Since Florence Nightingale established a nursing school in conjunction with St Thomas' Hospital in 1860, society has changed and particularly medical technology has undergone tremendous developments.